Mortality due to noncommunicable diseases in Brazil, 1990 to 2015, according to estimates from the Global Burden of Disease study - Malta, Deborah Carvalho; França, Elisabeth; Abreu, Daisy Maria Xavier; Perillo, Rosângela Durso; Salmen, Maíra Coube; Teixeira, Renato Azeredo; Passos, Valeria; Souza, Maria de Fátima Marinho; Mooney, Meghan; Naghavi, Mohsen (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Noncommunicable diseases (NCDs) are the leading health problem globally and generate high numbers of premature deaths and loss of quality of life. The aim here was to describe the major groups of causes of death due to NCDs and the ranking of the leading causes of premature death between 1990 and 2015, according to the Global Burden of Disease (GBD) 2015 study estimates for Brazil. DESIGN AND SETTING: Cross-sectional study covering Brazil and its 27 federal states. METHODS: This was a descriptive study on rates of mortality due to NCDs, with corrections for garbage codes and underreporting of deaths. RESULTS: This study shows the epidemiological transition in Brazil between 1990 and 2015, with increasing proportional mortality due to NCDs, followed by violence, and decreasing mortality due to communicable, maternal and neonatal causes within the global burden of diseases. NCDs had the highest mortality rates over the whole period, but with reductions in cardiovascular diseases, chronic respiratory diseases and cancer. Diabetes increased over this period. NCDs were the leading causes of premature death (30 to 69 years): ischemic heart diseases and cerebrovascular diseases, followed by interpersonal violence, traf- fic injuries and HIV/AIDS. CONCLUSION: The decline in mortality due to NCDs confirms that improvements in disease control have been achieved in Brazil. Nonetheless, the high mortality due to violence is a warning sign. Through maintaining the current decline in NCDs, Brazil should meet the target of 25% reduction proposed by the World Health Organization by 2025.